La enseñanza del español como lengua extranjera en Colombia: tópicos, tendencias y desafíos desde una revisión sistemática exploratoria - Lopez Yatacue, Froilan Esteban; Chamorro Mejía, Mónica (Colombian Applied Linguistics Journal, 2026)
This article presents a scoping review (SR) of trends and areas of interest in research on the teaching of Spanish as a foreign language (TSFL) in Colombia between 2013 and 2023. To this end, a corpus of 34 articles published in indexed journals was selected and analyzed. The findings reveal a significant increase in descriptive and exploratory publication in the field of TSFL during this period. Communicative, cultural, and intercultural competencies emerged as the most frequently researched themes, with a particular emphasis on communicative competence. Research activity is lead primarily by private universities, driven by foreign trade and international interaction. A sustained rise in publications is observed since 2014, which coincides with government policies and its national plan that promoted language learning in Colombia. The qualitative analysis highlights key terms such as language, research, learning, and teaching. Overall, the results point to the need for further research on intercultural competence and the development of teaching materials adapted to regional dialectal varieties. In addition, the collection of natural samples of natural language to create virtual didactic materials that reflect the linguistic particularities of the country.